Implementation of Library Management In Increasing Students' Interest In Reading At MA Hidayatul Mubtadiin Jatiagung, South Lampung Regency - Cipto Handoko (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
Library management is the process of planning, organizing, implementing, and controlling library management in a predetermined organization in the school library. Meanwhile, in increasing interest in reading, a motivation that librarians have in managing libraries and teachers participate in motivating students in increasing interest in reading. This research uses qualitative research methods with data collection techniques, in the form of observations, interviews, and documents While the findings in the field are: MA Hidayatul Mubtadiin Jatiagung South Lampung, has been quite good in implementing library management, but in carrying out an increase in student reading interest has not been maximized, on the other hand the teacher council does not motivate its students to visit the library in the school available at MA Hidayatul Mubtadiin Jatiagung. Meanwhile, the library space is still minimal and uncomfortable for students when they are in the library room. So the results of this study concluded that First, the Librarian and principal of MA Hidayatul Mubtadiin Jatiagung had carried out the implementation of library management quite well, directed and sustainable. Secondly, the principal of MA Hidayatul Mubtadiin Jatiagung has tried quite well in increasing students' interest in reading, by ordering the teacher council of each subject to become a member of the student's assignment or reading material recommended by the student council, but this is only limited to motivating students through assignments given by the teacher council to visit the library at the school.